FENOMENA COFFEE SHOP SEBAGAI GEJALA GAYA HIDUP BARU KAUM MUDA - Elly Herlyana (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2012)
Lifestyle of the juvenile tends to prestige and pragmatic orientedvalues. Furthermore, they like with every matter that can give impact on prestigeand modern image to their life. Lifestyle which is only to reach fun and joywithout thinking for further impact called as hedonistic. This is the view that weshould enjoy everything in this world fully. In addition, we proposed thequestions as follows: What are the general phenomena and the fact explanationthat can be asked on Coffee Shop as the hedonics style of the juvenile? Theresults of the studies based on evolutionism and the Islamic morality show thatthe characteristics of adolescents who tends to apply impulsive, love being thecenter of attention, tend to be part of it, and sensitive to new innovations tosupport hedonistic lifestyle trend. Such a lifestyle, it is a form of expression ofthe experimental behavior of teenagers held to try something new. Experimentalbehavior is still considered fair if it does not display a pattern of behavior that ismore dominant in the pleasures of life rather than learning. Islam's messageindicates that a life oriented to flesh and ignore the spirit is a mistake.